Table of contents and editorial information for Vol. 37, no. 1, Fall 2009 - Irma O'Dell; Mary Hale Tolar (Educational Considerations, 2009)
This content includes the table of contents, an editorial titled "Leadership Theories and Beyond: Application in Diverse Contexts" by the guest editors, and editorial information.